Development of ultrasonic tomography system for liquid/gas flow measurement in a vertical column - Nor Muzakkir Nor Ayob (School of Mechatronic, 2011)
The principal target of this research is to further exploit the capability of ultrasonic tomography imaging technique in providing valuable informationwith on-line monitoring solutionwhich can be deem as accountable feedback for improved process control to deter orminimise such maintenance process that arises. The potential of such system in determining the liquid and gas distribution as well as imaging the flow activities should have a widespread use such as food and beverage, oil and gas industries, petrochemical, water distribution, research laboratories and many more.